The College of Radiographers Research Strategy for the next five years. (October 2021) - Strudwick, R.; Harris, M.; McAlinney, H.; Plant, P.; Shuttleworth, P.; Woodley, J.; Harris, R.; O'Regan, T.
Abstract: This article outlines the updated College of Radiographers (CoR) Research Strategy. This new research strategy will shape the approach to research from the radiography profession over the next five years. This will apply to all the profession and is aspirational and future thinking. The updated research strategy is the fifth research strategy presented by the CoR. Over the last five years, there have been considerable developments within healthcare and healthcare research. As this article is being written we are still in the middle of a global pandemic (Covid-19) which has influenced all our lives. However, despite the challenges of the last year, we are in a stronger position as a profession with more radiographers working towards and gaining masters and doctoral level qualifications. There are more radiographers working in clinical academic roles and there has been further development of radiographers coordinating and delivering research as well as becoming research leaders. This updated research strategy supports the radiography profession in delivering research-based practice over the next five years offering a framework within which radiographers can develop.